Better Crash Data Can Improve Road Safety - Krambeck, Holly (World Bank, Washington, DC, 2018)
Low- and middle- income countries typically lack adequate systems for collecting road crash data. This limits their capacity to monitor, effectively advocate for, manage, and efficiently improve road safety. While many cities, states, and countries have adopted or developed proprietary systems for recording crash data, they are often developed in isolation, limiting the ability to share data among users. These systems may also be expensive - and unable to support road safety delivery and advocacy. They usually lack a seamless, global, real time, and georeferenced crash repository: a basis for monitoring the scale of the challenge. Data for road incident visualization evaluation and reporting (DRIVER) -a data collection system developed and now operating in the Philippines, answers this challenge, and offers an effective road safety support solution. DRIVER offers important opportunities for improved road safety data in many national and subnational jurisdictions, and its code is available free on the World Bank GitHub open source code repository. DRIVER is likely to become more widespread as the World Bank and the global road safety facility (GRSF) support its use in other countries and cities.